Cultural influences on online experiences, relationship quality, and customer engagement: A comparative study between Kuwait and Portugal - Al-Reesh, M. S.; Loureiro, S. M. C.; Bilro, R. G. (Multidisciplinary Business Review, 2025)
This paper investigates the interplay between online experiences, relationship quality, and customer inspiration in shaping customer engagement, focusing on two culturally distinct markets: Kuwait and Portugal. This study employed a quantitative research design using structured online surveys administered through Qualtrics panels service. Two distinct panels were used to collect data from general consumers in Portugal and Kuwait. The ﬁnal sample comprised 240 valid responses from Portugal and 210 from Kuwait. The ﬁndings highlight signiﬁcant cultural differences. Entertainment is a universally important aspect of online experiences, but informativeness is more critical in Kuwait, while social presence holds more importance in Portugal. Mediation analysis reveals that relationship quality (RQ) mediates the relationship between online experiences and engagement in Kuwait, emphasising the role of relational bonds in collectivist cultures. In contrast, customer inspiration serves as a consistent mediator across both contexts, with stronger effects in masculine cultures such as Kuwait. The results advance theoretical frameworks by integrating cultural dimensions and provide actionable insights for marketers to design culturally sensitive online strategies. The study underscores the importance of tailoring engagement approaches to cultural contexts, offering implications for theory development and practical applications in global marketing.